2022
DOI: 10.3389/fphar.2022.1007284
|View full text |Cite
|
Sign up to set email alerts
|

Hepatotoxic metabolites in Polygoni Multiflori Radix— Comparative toxicology in mice

Abstract: Polygoni Multiflori Radix (PM) and Rhei radix et rhizoma (rhubarb) contain similar hepatocyte-toxic anthraquinones such as emodin (major free anthraquinone in PM), physcion and their glycosides. In clinical practice, PM hepatotoxicity has been widely reported, although rhubarb is not recognized as hepatotoxic. To clarify the substances basis (key components) of PM hepatotoxicity, based on the characteristic components’ similarity within PM, rhubarb and their concocted forms, a comparative sub-acute toxicity st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“… Li D. et al (2022) identified 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucopyranoside (TSG), emodin, emodin-8-o-β-d-Glucopyranoside (EMG), and physcion as the primary PM metabolites responsible for liver damage ( Li D. et al, 2022 ). However, another study revealed only high-dose TSG combined with EMG induced liver lesions ( Wang et al, 2022 ). On the one hand, it is crucial to implement appropriate processing techniques for mitigating the hepatotoxicity of this otherwise non-toxic medicine.…”
Section: The Toxicity-effect Profile Of Toxic Tcmmentioning
confidence: 99%
“… Li D. et al (2022) identified 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucopyranoside (TSG), emodin, emodin-8-o-β-d-Glucopyranoside (EMG), and physcion as the primary PM metabolites responsible for liver damage ( Li D. et al, 2022 ). However, another study revealed only high-dose TSG combined with EMG induced liver lesions ( Wang et al, 2022 ). On the one hand, it is crucial to implement appropriate processing techniques for mitigating the hepatotoxicity of this otherwise non-toxic medicine.…”
Section: The Toxicity-effect Profile Of Toxic Tcmmentioning
confidence: 99%